Situación laboral de los comunicadores sociales de Babahoyo frente al nivel de satisfacción del ejercicio profesional - Gómez Triana, Isabel Carolina (2019)
The present case study called "LABOR SITUATION OF THE SOCIAL COMMUNICATORS OF BABAHOYO AGAINST THE LEVEL OF SATISFACTION OF THE PROFESSIONAL EXERCISE" has how to determine the employment situation of the social communicators of Babahoyo against the level of competence of the professional exercise, for this purpose employed a methodology of analysis and synthesis of the cases raised; A structured questionnaire questionnaire is required as an instrument, which specifies information on the academic training of professionals, their employment status, area of performance and the satisfaction they have with these categories. In this sense, after surveying the 120 professionals that make up the sample, the following findings will be determined, considering two factors to measure the satisfaction of social communication professionals; In this sense, the first was in terms of their job training, stating that they are satisfied and that this has allowed them to exercise independently or in various work activities. On the other hand, the second category is related to the satisfaction of their professional practice, thus demonstrating 30% satisfaction on average since they are happy with the exercise of their professional career. Although there is 11% of unemployed professionals who do not exercise any activity.